Short-term oral pre-exposure prophylaxis against HIV-1 modulates the transcriptome of foreskin tissue in young men in Africa - Petkov, Stefan; Herrera, Carolina; Else, Laura; Lebina, Limakatso; Opoka, Daniel; Seiphetlo, Thabiso B.; Pillay, Azure-Dee AP.; Mugaba, Susan; Namubiru, Patricia; Odoch, Geoffrey; Ssemata, Andrew S.; Serwanga, Jennifer; et al. (Frontiers in Immunology, 2022)
Whilst short-term oral pre-exposure prophylaxis (PrEP) with antiretroviral drugs in men who have sex with men has shown protection against HIV-1 infection, the impact of this regimen on the in vivo foreskin transcriptome is unknown. We collected foreskin tissue after voluntary medical male circumcision from 144 young men (72 from Uganda and 72 from South Africa) randomized to one to two doses of either oral tenofovir (TFV) disoproxil fumarate (FTC-TDF) or tenofovir alafenamide (FTC-TAF) or no drug (untreated controls). This novel approach allowed us to examine the impact of short-term oral PrEP on transcriptome of the male genital tract. A single dose of FTC-TDF did not affect the foreskin transcriptome in relation to control arm, however one dose of FTC-TAF induced upregulation of four genes AKAP8, KIAA0141, HSCB and METTL17. Following two doses of either FTC-TDF or FTC-TAF, there was an increase in 34 differentially expressed genes for FTC-TDF and 15 for FTC-TAF, with nine DEGs in common: KIAA0141, SAFB2, CACTIN, FXR2, AKAP8, HSCB, CLNS1A, DDX27 and DCAF15. Functional analysis of differentially expressed genes revealed modulation of biological processes related to mitochondrial stress (KIAA0141, HSCB and METTL17), anti-viral and anti-inflammatory pathways (CACTIN and AKAP8). Our results show that short-course on-demand oral PrEP in men modulates genes in foreskin tissue which are likely unfavorable to HIV acquisition and replication. We also describe an upregulated expression of genes involved in diverse mitochondria biology which may potentially result in worsened mitochondrial related functions. These results warrant further studies to assess the role of short-course and prolonged oral PrEP on biological processes of the foreskin mucosa.